2019
DOI: 10.1111/jgs.15859
|View full text |Cite
|
Sign up to set email alerts
|

Making and Measuring an Impact in a Digital World: The Role of Social Media and the Medical Journal

Abstract: This editorial comments on the article by https://doi.org/10.1111/jgs.15853 in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous studies have investigated the impact that other social media, such as Facebook or Instagram, have on a journal's impact [17][18][19][20][21]. All of these studies have shown that engagement on social media is predictive of journals having a greater impact.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the impact that other social media, such as Facebook or Instagram, have on a journal's impact [17][18][19][20][21]. All of these studies have shown that engagement on social media is predictive of journals having a greater impact.…”
Section: Discussionmentioning
confidence: 99%
“…7 The social media strategy for the Journal of the American Geriatrics Society included (1) allowing one color figure or visual per article for free; (2) encouraging the use of infographics or a chart or graph that represents the main findings of the article in tweets was evaluated before and after, and online mentions (measured via Altmetrics) increased significantly. 8,9 Similarly, the journal Gastrointestinal Endoscopy sought to identify if there was an association between social media posts about research articles and subsequent citations. They also used Altmetrics and found Twitter (tweets) had the largest predictive value, with Facebook and Mendeley also having a positive correlation.…”
Section: Introductionmentioning
confidence: 99%